Immunotherapy in conversion therapy for gastric cancer: current status, progress, and challenges - Su, Yi; Zhang, Xin; Deng, Wei (Frontiers in Oncology, 2025)
Gastric cancer remains a global health burden due to its late diagnosis and poor prognosis. Conversion therapy aims to make the initially unresectable tumor resectable through systemic treatment, providing the opportunity for long-term survival. The rise of immunotherapy has brought new potential to this field. Immunotherapy combined with chemotherapy, anti-angiogenic drugs or chemoradiotherapy has shown good efficacy in specific patients. This review summarizes the current evidence of conversion strategies based on immunotherapy, emphasizes key biomarkers, and explores the future direction of precise, multi-modal treatment.